NAVIGATING THE EVOLVING LEXICOLOGY LANDSCAPE: A SYSTEMATIC LITERATURE REVIEW - Zulianti, Irvitha (ELite Journal : International Journal of Education, Language and Literature, 2024)
The purpose of this literature review is to investigate recent developments in lexicology studies, covering trends, challenges, and opportunities impacting this domain. The systematic literature review method is used to collect, evaluate, and synthesize relevant scientific works in lexicology. Through careful searches across various academic databases and other sources. This study presents a systematic literature review (SLR) of emerging lexicology trends. Using the PRISMA protocol for study selection and digital tools such as Publish or Perish and Zotero for data analysis, this review selected and evaluated literature that met the predetermined inclusion criteria. , Then obtained the final results of 30 articles from these 2 databases and the findings of the review revealed several emerging trends in lexicology research, such as the integration of computational methods,  exploration of lexical variations, and an interdisciplinary approach to lexicon analysis. In addition, challenges in lexicography practices, such as managing large data sets, rapid language change, and lexical diversity, were identified, while opportunities for innovation in leveraging digital technologies and interdisciplinary collaboration were noted